A influência da corticoterapia antenatal na necessidade de reanimação e na mortalidade em recém-nascidos prematuros de muito baixo peso - Drummond, Sayonara (2013)
Objective: To evaluate the influence of antenatal corticosteroid therapy in resuscitation in the delivery room and mortality of newborns with birth weight less than or equal to 1,500 g and gestational age less than or equal to 34 weeks. Methods: Cohort study that we followed all newborns admitted to the NICU from January 2006 to December 2011. These were divided into two groups: those who received antenatal corticosteroids (n = 182) and those who did not (n=38). The main outcomes studied were the need for neonatal resuscitation, presence of neonatal morbidities during hospitalization and mortality. All variables that showed differences between the groups were evaluated by binary logistic regression. The statistical package SPSS 16.0 was used and significance was 0.05. Results: 220 patients were evaluated. There was no statistical difference between the groups in terms of birth weight, gestational age and the presence of major neonatal morbidity. Newborns who received antenatal corticosteroids required 2.4 times less resuscitation. Regarding advanced resuscitation, the group that received antenatal corticosteroids needed less endotracheal tube 3.7 times compared to the group not receiving and 5.7 times less cardiac massage. Drug use was 9 times less. The mortality rate was 3 times higher in the group that did not receive antenatal corticosteroids. Conclusion: Antenatal corticosteroid therapy reduced the need for resuscitation in the delivery room, especially the advanced resuscitation and mortality in newborn infants.